Room-temperature plastic deformation modes of cubic ZnS crystals. (1st April 2023) - Kitou, Shunsuke; Oshima, Yu; Nakamura, Atsutomo; Matsunaga, Katsuyuki; Sawa, Hiroshi
Abstract: Light environment drastically alters the plasticity of zinc sulfide (ZnS) single crystals: they exhibit ductility in darkness while brittleness in lights. This study investigated their microscopic deformation modes of the light-environment-dependent plasticity, by using synchrotron X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning TEM (STEM) measurements. The XRD analyses disclosed that the ZnS crystals originally have two domains with almost the same volume fraction with a twin relationship and plastically deform in darkness, accompanying changes in the domain volume ratio (namely extinction of twins). It was also observed that the domain volume ratios become constant to be 0.2 at more than 10% plastic strains. The STEM analyses indicated that the deformation mode in darkness switches at around 10% plastic strain from slip deformation by glide of isolated partial dislocations to by simultaneous glide of paired partials inside the major domains. Although ZnS single crystals exhibited only a few percent of plastic strains in lights, localized glide of isolated partials and the resultant changes in domain volume ratios similar to in darkness were confirmed. That is, the deformation modes of ZnS at the initial stage were similar regardless of light environments although the macroscopic deformation behaviors were quite different. Graphical abstract: Image, graphical abstract